O urbanismo modernista em Minas Gerais: o caso "Ipatinga" - Roxane Sidney Resende de Mendonca (2006)
The objective of this Master Thesis is to evaluate whether the post-modern criticism is pertinent to Ipatinga, a modern city of Minas Gerais that was built with the steel plant USIMINAS to house its workers. The argument made here is that modernism-planning concepts of the Athens Charter were applied - in Brazil - to a different context than the onefrom which they had originated in Europe and in the United States. However, Brazilian scholars have accepted the criticism to modernism urban planning without verifying whether it was pertinent or not to our projected cities. This argument is based on a comparative studybetween the projected part of Ipatinga and the part that was built without a general plan. Initially, the theoretical framework of the research is presented, justifying the importance of re-evaluating the post-modern criticism as far as Brazilian cities are concerned. Secondly, the historical and conceptual references are discussed and USIMINAS Vila-Operária is presented. The concepts that apply to the comparative study between the projected part of Ipatinga and the part that was built without planning are discussed next. Four suburbs have been chosen: two that belong to the Vila-Operária (Cariru and Novo Cruzeiro) and two that developed in accordance with real estate market (Cidade Nobre e Bom Jardim). Thecomparison between the two situations analyzed - the "artificial" and the "spontaneous" is made in accordance to the post-modern criticism, particularly that one put forward by Lefèbvre (1969,1999), Jacobs (2000) and Alexander (1967). It is concluded that Ipatinga is a rich laboratory for investigating whether post-modern criticism applies to the Brazilian case. The analyzed situations show that one doesnt have to consider that modernism concepts have failed in Brazil. Conversely, Ipatinga discloses that critical scrutinizing of urban problems is fundamental, since peculiarities exist. Modernism rules can be excellent to preserve the environmental qualities of suburbs, the sunlight and the vegetation, but at the same time they can become antiquated if adopted as closed andrigid models.